Systems analysis and design - Dennis, Alan (John Wiley & Sons, 2010)
This book offers a hand-on, project-based approach that focus on the core set of skills that all analysts need to know. Building on their experiences as professional systems analysts and award-winning teachers, the authors capture the experiece of developing and analyzing systems.